Cernunnos/XLF promotes the ligation of mismatched and noncohesive DNA ends - Tsai, Chun J. (National Academy of Sciences, 2007)
Nonhomologous end-joining (NHEJ) repairs DNA double-strand breaks created by ionizing radiation or V(D)J recombination of the immunoglobulin genes. The breaks often leave mismatched or nonligatable ends, and NHEJ must repair the breaks with high efficiency and minimal nucleotide loss. Here, the NHEJ proteins Ku, DNA-dependent protein kinase catalytic subunit, XRCC4/Ligase IV, and Cernunnos/XRCC4-like factor joined mismatched and noncohesive DNA ends in the absence of processing factors. Depending on the mismatch, Cernunnos stimulated joining 8- to 150-fold. For substrates with a blunt end and a 3′ overhanging end, Ku, XRCC4/Ligase IV, and Cernunnos ligated the 3′ overhanging hydroxyl group to the 5′ phosphate of the blunt end, leaving the other strand unjoined. This activity provides a mechanism for retaining 3′ overhang sequences, as observed during V(D)J recombination in vivo. Thus, Cernunnos/XRCC4-like factor promotes a mismatched end (MEnd) DNA ligase activity to facilitate joining and to preserve DNA sequence. Furthermore, MEnd ligase activity may have applications in recombinant DNA technology.